2019
DOI: 10.1055/s-0039-1700872
|View full text |Cite
|
Sign up to set email alerts
|

Individual Patient Data Pooled Analysis of Randomized Trials of Bivalirudin versus Heparin in Acute Myocardial Infarction: Rationale and Methodology

Abstract: Background Individual randomized controlled trials (RCTs) of periprocedural anticoagulation with bivalirudin versus heparin during percutaneous coronary intervention (PCI) have reported conflicting results. Study-level meta-analyses lack granularity to adjust for confounders, explore heterogeneity, or identify subgroups that may particularly benefit or be harmed. Objective To overcome these limitations, we sought to develop an individual patient-data pooled database of RCTs comparing bivalirudin vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Parenteral anticoagulants such as bivalirudin, argatroban, and fondaparinux have been studied in management of patients with acute coronary syndromes, VTE, and heparin-induced thrombocytopenia. 47,48 However, these agents are more expensive than unfractionated heparin or LMWH, and there are limited data about their use in COVID-19.…”
Section: Other Parenteral Anticoagulantsmentioning
confidence: 99%
“…Parenteral anticoagulants such as bivalirudin, argatroban, and fondaparinux have been studied in management of patients with acute coronary syndromes, VTE, and heparin-induced thrombocytopenia. 47,48 However, these agents are more expensive than unfractionated heparin or LMWH, and there are limited data about their use in COVID-19.…”
Section: Other Parenteral Anticoagulantsmentioning
confidence: 99%
“…Study-level meta-analyses have shown that in patients with STEMI undergoing primary PCI, periprocedural bivalirudin compared with heparin ± glycoprotein IIb/IIIa inhibitors reduces the risk of major bleeding, increases the risk of acute stent thrombosis, and in some studies, a short-term mortality benefit was observed [ 10 , 12 , 32 , 33 ]. Additionally, a recent individual patient-level meta-analysis echoed the latter findings and confirmed a reduced risk of death at 30 days for bivalirudin compared with heparin ± glycoprotein IIb/IIIa inhibitors in patients with STEMI undergoing primary PCI [ 34 , 35 ]. However, individual randomised controlled trials have reported conflicting results reflecting the considerable heterogeneity between trials.…”
Section: Discussionmentioning
confidence: 86%
“…Subsequent trials used glycoprotein IIb/IIIa inhibitors selectively, with some reporting no bleeding reduction with bivalirudin [ 17 , 38 ], while in others, a reduction in major bleeding was observed irrespective of glycoprotein IIb/IIIa inhibitor use [ 18 , 21 , 39 ]. Considering the totality of the evidence, the bleeding advantage observed with bivalirudin is likely independent of planned glycoprotein IIb/IIIa inhibitor use in the heparin arm, as confirmed in a recent individual patient-level meta-analysis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 87%
“…43,44 Of note, a large patient-level meta-analysis of eight RCTs comparing bivalirudin without systematic GPI to heparin (UFH or low-molecular-weight heparin) with or without systematic GPI and comprising 27,409 patients with STEMI or non-STEMI (NSTEMI) was recently presented. 45 This study found that in patients with STEMI undergoing PCI, use of bivalirudin was associated with a significant reduction of cardiac mortality (adjusted hazard ratio [aHR]: 0.72. 95% confidence interval [CI]: 0.57-0.91) and serious bleeding (aHR: 0.57, 95% CI: 0.47-0.68) at 30 days, albeit at the cost of increased risk of reinfarction (aHR: 1.29, 95% CI: 1.02-1.64) and stent thrombosis (aHR: 1.45, 95% CI: 1.05-1.91).…”
Section: Antiplatelet Therapymentioning
confidence: 96%